ANALISIS YURIDIS KETENTUAN PERTANGGUNGJAWABAN PIDANA BAGI PELAKU PROSTITUSI ONLINE DI INDONESIA - Febri Dwi Yanto (Legal Spirit, 2017)
Straubhaar said that the rapid use of the Internet becomes the dominant force leading to the development of a growing phenomenon in the society. This is in line with the development activities of the new prostitution making use of internet media online. Factually, many cases found in the mass media about the online prostitution may cause public to unrest. Based on the research results, it was shown that a provision regulating online prostitution as a criminal offense in Indonesia is regulated in some Acts with sectoral and casuistic in nature, among others the Criminal Law, the Law No. 11 in the year of 2008 on Information and Electronic Transactions, the Law Number 44 in the Year of 2008 on Pornography, Law Number 21 in the Year of 2007 on Combating Trafficking in Persons and Law No. 35 in the year of 2014 on Child Protection. Among the five earlier Acts, ITE Act and Pornography Act are the most comprehensive laws to regulate the provision of online prostitution because it regulates electronic documents or electronic information as a medium in online prostitution. Secondly, the provisions of criminal accountability for perpetrators of online prostitution in Indonesia are based on the four subjects namely: implementing maker (plegen) consists of pimps, prostitutes and sex workers as well as the manufacturer's tenants participants (mede pleger) consisting of the owner user / server an online prostitution website. Keywords: Criminal Liability, Actors, Online Prostitution